Coupling Technology of Deep-Hole Presplitting Blasting and Hydraulic Fracturing Enhance Permeability Technology in Low-Permeability and Gas Outburst Coal Seam: A Case Study in the No. 8 Mine of Pingdingshan, China - Wei Wang; Yanzhao Wei; Minggong Guo; Yanzhi Li (Advances in Civil Engineering)
The current study aims to analyze the principles of integrated technology of explosion to tackle the problems of coal seam high gas content and pressure, developed faults, complex structure, low coal seam permeability, and high outburst risk. Based on this, we found through numerical simulation that as the inclination of the coal seam increases, the risk of coal and gas outburst increases during the tunneling process. Therefore, it is necessary to take measures to reduce the risk of coal and gas outburst. We conducted field engineering experiments. Our results show that the synergistic antireflection technology of hydraulic fracturing and deep-hole presplitting blasting has a significant antireflection effect in low-permeability coal seams. After implementing this technology, the distribution of coal moisture content was relatively uniform and improved the influence range of direction and tendency. Following 52 days of extraction, the average extraction concentration was 2.9 times that of the coal seam gas extraction concentration under the original technology. The average scalar volume of single hole gas extraction was increased by 7.7 times. Through field tests, the purpose of pressure relief and permeability enhancement in low-permeability coal seams was achieved. Moreover, the effect of gas drainage and treatment in low-permeability coal seams was improved, and the applicability, effectiveness, and safety of underground hydraulic fracturing and antireflection technology in low-permeability coal seams were verified. The new technique is promising for preventing and controlling gas hazards in the future.